2021
DOI: 10.1051/0004-6361/202141094
|View full text |Cite
|
Sign up to set email alerts
|

Lithium depletion and angular momentum transport in F-type and G-type stars in Galactic open clusters

Abstract: Context. Open clusters provide unambiguous clues to understand the evolution of 7Li at the surface of low-mass stars and its possible correlation with stellar rotation, which is a challenge for both stellar hydrodynamics and Galactic chemical evolution. Aims. We aim to quantify the efficiency of the transport processes for both angular momentum and chemicals that are required to explain simultaneously the observed behaviour of surface 7Li (and 9Be) and rotation as well as the internal rotation profiles inferre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 164 publications
(194 reference statements)
5
11
0
Order By: Relevance
“…More metallic stars with larger conv ectiv e masses (larger markers) present lower Li content. This depletion according to metallicity is qualitatively in line with the works of Castro et al ( 2008 ) and Dumont et al ( 2021b ).…”
Section: R E S U Lt S a N D Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…More metallic stars with larger conv ectiv e masses (larger markers) present lower Li content. This depletion according to metallicity is qualitatively in line with the works of Castro et al ( 2008 ) and Dumont et al ( 2021b ).…”
Section: R E S U Lt S a N D Discussionsupporting
confidence: 88%
“…Qualitatively, our strong anticorrelation with age is in line with non-standard models of Li depletion (Charbonnel & Talon 2005 ;Nascimento et al 2009 ;Xiong & Deng 2009 ;Denissenkov 2010 ;Andr ássy & Spruit 2015 ), as those models are constructed to reproduce the low Li observed in the solar photosphere. The strong anticorrelation with metallicity observed in our sample is also within the predictions of non-standard models, due to the deepening of the convection zone (Castro et al 2008 ;Dumont et al 2021b ). Ho we ver, there is a lack of detailed predictions of Li depletion both with age and metallicity, preventing more detailed comparisons with our results.…”
Section: O N C L U S I O N Ssupporting
confidence: 88%
“…Nondetections are not displayed; some error bars are too small to be visible. (Dumont et al 2021), the lithium dip has been observed in M35, the Hyades, open clusters a few billion years old, and even field stars (Steinhauer & Deliyannis 2004). However, it has not been found in the Pleiades (Soderblom et al 1993).…”
Section: Ew Analysis-li λ6707mentioning
confidence: 95%
“…Presently predicted Li abundances are a factor of 3 beyond the Spite plateau. Certainly stellar effects, depleting Li, have to be considered (Dumont et al 2021) and there exist clear indications that this is the case (Korn 2020;Fields and Olive 2022), but physics beyond the standard model might also be required on the theory side, for details see the white paper by Grohs et al (2019).…”
Section: Uncertainties and Further Aspectsmentioning
confidence: 99%